Analysis of the Effect of Job Satisfaction and Loyalty on Employee Performance at PT Kedungdoro Jaya Indo Surabaya - Eduardus Nanggur; Rohmah Kurniawati (Information Technology and Science (ITScience), 2025)
In an increasingly competitive business world, one of the factors that determine the company's success is employee performance. Optimal performance is strongly influenced by various factors, two of which are job satisfaction and employee loyalty. Job satisfaction refers to how employees feel about their jobs, while loyalty describes the level of loyalty and commitment to the company PT Kedungdoro Jaya Indo Surabaya. Employees who feel satisfied with their jobs tend to show high loyalty, which in turn can increase productivity and performance, especially at PT Kedungdoro Jaya Indo Surabaya. The purpose of this study was to determine and analyze job satisfaction, customer loyalty affect employee performance partially and simultaneously at PT Kedungndoro Jaya Indo Surabaya. The type of research used is quantitative research. the population in this study were 40 employees of PT Kedungndoro Jaya Indo Surabaya. Data collection techniques Questionnaires or questionnaires and documentation. The analysis technique used is multiple linear regression. The results of this study are Employee satisfaction affects employee performance partially at PT Kedungdoro Jaya Indo Surabaya. Employee loyalty partially affects employee performance at PT Kedungdoro Jaya Indo Surabaya. Employee satisfaction and employee loyalty affect employee performance simultaneously at PT Kedungdoro Jaya Indo Surabaya.